Clonal Propagation of some Bamboo Species through Adventitious Rhizogenesis in Culm Cuttings - Nain, N. P. S.; Meena, S. L.; Kunjam, K. K.; Tripathi, S. P.; Singh, Sanjay (Indian Forester, 2007)
With a view to evolve cloning procedure for Bambusa multiplex, Bambusa tulda and Bambusa vulgaris single node culm cuttings were subjected to four different treatments for 24h viz., water, or 1, 2 and 4 mM NAA. The treated cuttings were horizontally placed and covered completely with sand in ground beds of low-cost mist chamber. After two months, the cuttings were scored for adventitious rooting percentage, root number and length. Significant influence of graded concentrations of NAA on adventitious rhizogenesis was observed. In B. tulda and B. vulgaris the treatment of 4 mM NAA to culm cuttings proved superior for root induction while 2mM was found best for rooting in B. multiplex.